Vibrational multi-reference coupled cluster theory in bosonic representation - Banik, Subrata; Pal, Sourav; Prasad, M. Durga (Journal of Chemical Physics, 2012)
The vibrational multi-reference coupled cluster method is developed to calculate the vibrational excitation energies of polyatomic molecules. The method is implemented on ozone and formaldehyde molecules and the results are compared with full vibrational configuration interaction (FVCI) method. A good agreement is found between the vibrational multi-reference coupled cluster method and converged FVCI method for lower lying vibrational states. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4753422]